Quality improvement initiative: improving proportion of preterm infants on mothers only milk at the time of discharge - Kaur, Sumandeep; Kaur, Gurmeet; Rawat, H. C. L.; Bansal, Prajjwal; Sethi, Amanpreet (International Journal of Contemporary Pediatrics, 2019)
Background: Availability of mothers only milk (MOM) for preterm infants is a boon for their growth and development. Authors found that in our Special Newborn Care Unit (SNCU), the availability of MOM was very less with excessive use of formula feed. So, authors planned a quality improvement (QI) study to improve availability of MOM for preterms in level 3 SNCU catering to both in-born and out-born neonates. Methods: Authors aimed to improve availability of MOM to preterm infants admitted in SNCU from the current 10% to 80% at day 7 of admission over a period of 8 weeks. Authors included preterm and mother dyads with <34 weeks of gestation or having birth weight <1800 gm. and likely to stay in SNCU for at least a week. For this initiative a QI team was formed. Baseline data was collected for a period of 3 weeks and analysis was performed of various constrains in providing MOM to preterms was later an interventional package was implemented which included counselling to mothers, Kangaroo mother care (KMC), demonstration of milk expression techniques. Intervention phase was implemented for the period of 8 weeks followed by sustenance phase for 2 months. Results: Proportion of preterm infants on MOM increased from 10% to 81% during intervention phase at day 7 of admission and remained 66% during sustenance phase. Conclusion: QI initiative has the potential to bring a tremendous change in making mothers milk available to both inborn and out-born preterms. With existing resources simple interventions can increase availability of MOM to preterm infants.